PENGARUH PEMBELAJARAN PENDEKATAN SAINTIFIK DAN VARIASI GAYA MENGAJAR TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Muhammad Lukman; Risnawati Risnawati; Nurhasanah Bakhtiar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This study aims to examine the influence of scientific approach learning and variation in teaching style on students’learning motivationat junior high schools in Marpoyan Damai District, Pekanbaru. This research was correlational research including in quantitative approach. This research used random sampling as the sampling technique. Data were analyzed by using simple regression, multiple regression and coefficient of determination (r2) techniques. The results of data analysis showed that firstly, there was a significant influence of scientific approach learning on students’learning motivation at state junior high schools in Marpoyan Damai District, Pekanbaru with a level of influence of 0.279 and the significant value of 0,000 <0.05, secondly, there was a significant influence of variation inteaching style on students’learning motivation at state junior high schools in Marpoyan Damai District, Pekanbaru with a level of influence of 0.226 and the significant value of 0,000 <0.05, and lastly, there was a significant influence of scientific approach learning and variationin teaching style on students' learning motivation with a significant value of 0,000 <0.05 and the percentage of R2 (R square) of 0.090 or (9%). It shows that the percentage of contribution of independent variables (the learning of scientific approach and variation inteaching style) on the dependent variable (student motivation) was 9% meanwhile the remains (91%) were influenced by other variables.